The presence of European and Asian natural medicine in Ricardo Palma’s «¡A nadar, peces! - Zamalloa Astorga, Sebastián Fidel (2020)
This article takes the Peruvian story «¡A nadar, peces!», written by Ricardo Palma, as a point of reference. In this paper, an analysis will be made of the plants and natural products with medicinal properties of European or Asian origin that are mentioned in the mentioned text. The aim is to define the arrival of these elements to the national territory during the Viceroyalty, the characteristics and the different uses that make them qualify as natural remedies. It also seeks to argue about the importance of the field to which they belong: naturopathy.